ANALISIS KINERJA DINAS KEBUDAYAAN DAN PARIWISATA KOTA SEMARANG - Indah Permatasari; Nina Widowati; Aloysius Rengga (Journal of Public Policy and Management Review, 2013)
This study aims to describe and analyze the performance of the Dinas Kebudayaan dan Pariwisata Kota Semarang, to know the problems that become an obstacle to the performance of the organization and to find out how to overcome the performance bottleneck. This study used qualitative research methods. Performance of Dinas Kebudayaan dan Pariwisata Kota Semarang not shown optimal results. It can be seen from the mission has not been accomplished, including the unavailability of professional human resources as needed, inadequate infrastructure and the absence of a partnership with other parties. For that, it needs to be revisited workload of each employee so that vision and mission can be implemented optimally.